A method for optimizing heat treatment process of rare earth Ce modified Al-Si-Mg based casting alloy based on computational thermodynamics

CN122466372BActive Publication Date: 2026-10-09南宁桂电电子科技研究院有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610924132.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-09
Estimated Expiration
2046-06-25

AI Technical Summary

Technical Problem

这种经验式方法存在明显缺陷:一方面,固定工艺窗口难以适应再生铝合金成分批次波动大的实际情况,导致工艺窗口狭窄、合金性能波动大;另一方面,大量交叉实验带来高昂的时间与经济成本,且无法从热力学本质上解析上述双重约束的温度边界,使工艺制定带有盲目性

Benefits of technology

[0024] I. Quantitative design of heat treatment process parameters for Ce-containing cast aluminum alloys was achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122466372B_ABST
    Figure CN122466372B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of based on computational thermodynamics optimization rare earth Ce modified Al-Si-Mg base casting alloy heat treatment process method, belong to casting aluminum alloy heat treatment technical field.The steps of the method of the present application include: constructing thermodynamic database, the solid solution temperature curve of Mg2Si aging strengthening phase in the alloy to be handled, the equilibrium dissolution temperature of AlSiCe rare earth phase and the influence law of Ce element on Al matrix vacancy formation energy;Select temperature interval as solid solution treatment window, carry out solid solution treatment and quenching cooling to form supersaturated solid solution;Subsequently, artificial aging treatment is carried out, and the aging temperature is determined according to the influence law of the vacancy formation energy.The present application accurately determines the temperature window by thermodynamic calculation, which takes into account the full solid solution of Mg2Si phase and the thermal stability of AlSiCe rare earth phase, realizes the synergistic regulation of aging strengthening phase and rare earth phase, and effectively improves the comprehensive mechanical properties of alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heat treatment technology for cast aluminum alloys, and specifically to a method for optimizing the heat treatment process of rare earth Ce-modified Al-Si-Mg-based cast alloys based on computational thermodynamics. Background Technology

[0002] Al-Si-Mg cast aluminum alloys are widely used in automotive lightweighting and aerospace fields due to their excellent casting fluidity and high specific strength. With the rapid development of the recycled aluminum industry, the problem of iron impurities accumulating generation by generation during the waste aluminum recycling process has become increasingly prominent. Iron has extremely low equilibrium solid solubility in the aluminum matrix, and during solidification, it easily forms coarse, acicular, brittle iron-rich phases such as β-Al5FeSi, severely disrupting the continuity of the matrix and becoming a stress concentration source and crack initiation nucleus, leading to a sharp deterioration in the alloy's plasticity and toughness. This problem is a core metallurgical bottleneck restricting the high-value utilization of recycled Al-Si-Mg cast alloys.

[0003] Rare earth cerium (Ce) has significant multi-faceted microstructure regulation effects on Al-Si-Mg alloys due to its relatively abundant resources and controllable costs. As a surface-active element, Ce can refine α-Al grains; it can adsorb at the eutectic silicon growth front, causing it to transform from a lamellar to a fibrous structure; and it can undergo alloying reactions with iron impurities, promoting the transformation of acicular β-Al5FeSi phases into less harmful cerium-containing multi-component phases. These three effects make cerium a highly promising microalloying element. However, the introduction of cerium also further complicates the already complex Al-Si-Mg system metallurgically. The solidification microstructure of the alloy simultaneously contains the Mg2Si age-strengthening phase, the eutectic Si phase, various iron-rich phases, and the AlSiCe rare earth phase, with each phase exhibiting highly competitive thermodynamic stability and precipitation behavior. In particular, the responses of Mg2Si and AlSiCe phases in subsequent heat treatment processes are diametrically opposed: Mg2Si requires a high solution temperature to achieve full dissolution, providing sufficient thermodynamic driving force for subsequent aging strengthening; while AlSiCe phase, as a stable intermetallic compound, may dissolve or even partially melt at excessively high solution temperatures. Once it loses its structural integrity, its stabilizing effect on iron impurities will be irreversibly lost, and the bound iron atoms may reprecipitate as harmful needle-like phases.

[0004] Therefore, for the heat treatment process of Ce-modified Al-Si-Mg-based cast alloys, the thermodynamic antagonistic constraints of "full solution of Mg2Si" and "insolubility of AlSiCe rare earth phases" must be simultaneously satisfied in a single solution treatment step. The feasible process window under this constraint is highly sensitive to the alloy composition and shifts significantly with changes in Ce content. For a long time, the determination of heat treatment process parameters for such alloys has mainly relied on recommended values ​​from empirical manuals or multiple rounds of orthogonal experimental screening. This empirical method has significant drawbacks: on the one hand, a fixed process window is difficult to adapt to the large batch-to-batch fluctuations in the composition of recycled aluminum alloys, resulting in a narrow process window and large fluctuations in alloy properties; on the other hand, numerous cross-experiments bring high time and economic costs and cannot analyze the temperature boundaries of the aforementioned dual constraints from a thermodynamic perspective, making process formulation somewhat arbitrary.

[0005] Integrated computational materials engineering, centered on the CALPHAD method and based on the principle of Gibbs free energy minimization, can quantitatively calculate the phase equilibrium and phase transformation behavior of multi-component alloy systems through modeling, playing a significant role in the design of new alloy compositions. However, current engineering applications of this method are mainly limited to solidification path prediction and composition screening, with a significant gap in guiding the precise design of heat treatment processes for alloys with given compositions. The key reason for this gap lies in the long-standing incompleteness of the thermodynamic database for the Al-Si-Mg-Fe-Ce pentagonal system. This system encompasses ten boundary binary and ten boundary ternary systems, with inconsistent thermodynamic parameters from various sources. Furthermore, the phase equilibrium relationships at the aluminum-rich end and the thermal stability data of intermetallic compounds in the crucial Al-Fe-Ce ternary subsystem remain inaccurate, resulting in a lack of reliable foundation for directly constructing a thermodynamic description of the pentagonal system.

[0006] The above situation reflects the lack of an optimization method in this field that can quantitatively correlate thermodynamic calculations with process parameters throughout the entire heat treatment process. Summary of the Invention

[0007] To address the aforementioned problems, this invention provides a method for optimizing the heat treatment process of rare-earth Ce-modified Al-Si-Mg-based casting alloys based on computational thermodynamics. By constructing a five-element thermodynamic database of Al-Si-Mg-Fe-Ce, the critical window between the full solid solution temperature of Mg2Si and the equilibrium dissolution temperature of the AlSiCe phase is accurately calculated. This solves the contradiction between the traditional T6 process and the inability to simultaneously achieve full solid solution of Mg2Si and the thermal stability of rare-earth phases, realizing the synergistic strengthening of nano-coherent precipitates and β″-Mg2Si, and breaking through the technical bottleneck of simultaneously improving the strength and plasticity of high-iron aluminum alloys.

[0008] To achieve the above technical objectives, the present invention adopts the following technical solution:

[0009] A method for optimizing the heat treatment process of rare-earth Ce-modified Al-Si-Mg-based casting alloys based on computational thermodynamics includes the following steps:

[0010] S1. Provide a rare earth Ce-modified Al-Si-Mg based casting alloy to be treated. Using the Al-rich Al-Si-Mg-Fe-Ce pentagonal system thermodynamic database, calculate the solid solution temperature curve of the Mg2Si age-strengthening phase, the equilibrium dissolution temperature of the AlSiCe rare earth phase, and the influence of Ce element on the Al matrix vacancy formation energy in the casting alloy.

[0011] S2. Based on the calculation results of step S1, select the temperature range between the full solid solution temperature of Mg2Si phase and the equilibrium dissolution temperature of AlSiCe rare earth phase as the solid solution treatment window, and perform solid solution treatment on the casting alloy within the solid solution treatment window.

[0012] S3. The alloy after the solution treatment in step S2 is quenched and cooled to form an Al-based supersaturated solid solution.

[0013] S4. Perform artificial aging treatment on the alloy after quenching in step S3. The aging temperature is determined based on the influence of Ce element on the vacancy formation energy of Al matrix calculated in step S1.

[0014] Preferably, the pentaneous system thermodynamic database in step S1 is constructed based on the CALPHAD method, and the thermodynamic model parameters of each equilibrium phase are fitted by the PARROT optimization module.

[0015] Preferably, the casting alloy to be treated in step S1 belongs to the Al-Si-Mg-Fe-Ce pentagonal alloy system, wherein the amount of Ce added is 0.2-1.8 wt.%.

[0016] Preferably, in the thermodynamic database mentioned in step S1, the isothermal cross-sectional phase equilibrium data of the Al-Fe-Ce ternary system are combined with the thermodynamic data of the Al-Si-Mg, Al-Si-Fe, Al-Si-Ce, Al-Mg-Fe, and Al-Mg-Ce binary and ternary subsystems. The thermodynamic description parameters of the AlSiCe rare earth phase in the Al-Si-Mg-Fe-Ce pentagonal system are obtained by CALPHAD extrapolation, and the equilibrium dissolution temperature of the AlSiCe rare earth phase is determined based on the thermodynamic description parameters.

[0017] Preferably, the selection of the solid solution treatment window in step S2 is based on the following criteria: the solid solution temperature is set above the complete solid solution temperature of the Mg2Si phase calculated by the thermodynamic database and below the equilibrium dissolution temperature of the AlSiCe rare earth phase.

[0018] Preferably, in step S2, the solution treatment temperature is 520-545℃.

[0019] Preferably, in step S2, the heat preservation time for the solution treatment is 6-12 hours.

[0020] Preferably, the quenching medium used for quenching and cooling in step S3 is water or a mixture of ice and water, and the quenching transfer time does not exceed 15 seconds.

[0021] Preferably, the heat preservation time for artificial aging treatment in step S4 is 4-10 hours.

[0022] Preferably, the aging temperature for the artificial aging treatment in step S4 is 160-190℃.

[0023] Compared with the prior art, the present invention has the following advantages and technical effects:

[0024] I. Quantitative design of heat treatment process parameters for Ce-containing cast aluminum alloys was achieved.

[0025] The determination of heat treatment process parameters for existing Al-Si-Mg cast aluminum alloys mainly relies on empirical trial-and-error methods or orthogonal experimental screening, lacking a quantitative design basis that can simultaneously consider the solid solution behavior of the Mg2Si phase and the thermal stability of the Ce rare earth phase. This invention utilizes the thermodynamic database of the Al-rich Al-Si-Mg-Fe-Ce pentagonal system to pre-calculate three key thermodynamic parameters before solution treatment: the solid solution temperature curve of the Mg2Si aging-strengthening phase, the equilibrium dissolution temperature of the AlSiCe rare earth phase, and the influence of Ce on the vacancy formation energy of the Al matrix. This elevates the selection of the solid solution temperature window and the determination of the aging temperature from empirical judgment to quantitative deduction based on phase equilibrium and defect thermodynamics, significantly reducing the reliance on repeatable experiments in process development.

[0026] Second, it resolved the contradiction between the complete re-dissolution of the Mg2Si phase and the thermal stability of the AlSiCe rare earth phase during solution treatment.

[0027] Ce-modified Al-Si-Mg casting alloys face inherent contradictions during solution treatment: if the solution temperature is too low, the Mg2Si aging-strengthening phase cannot be completely dissolved back into the α-Al matrix, resulting in insufficient driving force for subsequent aging precipitation; if the solution temperature is too high, the AlSiCe rare-earth phase may partially or completely dissolve, losing its stabilizing effect on Fe impurities, causing the acicular iron-rich phase to re-precipitate and disrupt the matrix. This invention uses the thermodynamically calculated complete solution temperature of the Mg2Si phase as the lower limit of the solution temperature and the equilibrium dissolution temperature of the AlSiCe rare-earth phase as the upper limit, precisely selecting a temperature window between the two for solution treatment. This ensures that the Mg2Si phase fully dissolves to form a highly supersaturated solid solution while maintaining the structural stability of the AlSiCe rare-earth phase, preventing complete dissolution during the solution process and allowing it to continue to solidify Fe impurities.

[0028] III. Controlled precipitation of Ce during aging process achieved by controlling vacancy formation energy.

[0029] Conventional heat treatment processes do not involve targeted control of rare earth element precipitation behavior when selecting aging temperatures. When Ce precipitates uncontrolledly during aging, it may form coarse, incoherent precipitates that fail to contribute to strengthening. This invention pre-calculates the influence of Ce on the vacancy formation energy of the Al matrix and determines the aging temperature range based on this calculation. This allows Ce atoms dissolved in the α-Al matrix to precipitate in a controlled manner as nanoscale Al-Ce-Si coherent precipitates during the aging stage, thus avoiding the formation of coarse, incoherent phases.

[0030] IV. A multi-strength microstructure was formed, consisting of β″-Mg2Si phase and Al-Ce-Si coherent precipitates.

[0031] For high-Fe content recycled Al-Si-Mg cast alloys, conventional heat treatment strengthens the alloy solely through the β″-Mg2Si aging strengthening phase. However, the residual acicular iron-rich phases in the as-cast microstructure have a disruptive effect on the matrix, limiting the full extent of the strengthening effect. This invention, through the synergistic control of the solution temperature window and aging temperature range, constructs a microstructure in the α-Al matrix where the β″-Mg2Si aging strengthening phase and the Al-Ce-Si coherent precipitate coexist. The latter maintains a coherent or semi-coherent crystallographic matching relationship with the matrix. These two types of nanoscale precipitates are dispersed in the matrix, creating multiple pinning effects on dislocation slip and climb, introducing a second precipitation strengthening contribution induced by rare earth elements on top of conventional precipitation strengthening. Attached Figure Description

[0032] Figure 1 This is a transmission electron microscope image of the alloy of the present invention in its heat-treated state;

[0033] Figure 2This is a SEM image of the alloy in the heat-treated state of the present invention;

[0034] Figure 3 This is a surface distribution diagram of Al element in the alloy of this invention;

[0035] Figure 4 This is a surface distribution diagram of Si element in the alloy of this invention;

[0036] Figure 5 This is a surface distribution diagram of Mg element in the alloy of this invention;

[0037] Figure 6 This is a surface distribution diagram of Fe element in the alloy of this invention;

[0038] Figure 7 This is a surface distribution diagram of Ce element in the alloy of this invention. Detailed Implementation

[0039] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0040] A method for optimizing the heat treatment process of rare-earth Ce-modified Al-Si-Mg-based casting alloys based on computational thermodynamics includes the following steps:

[0041] S1. Provide a rare earth Ce-modified Al-Si-Mg based casting alloy to be treated. Using the Al-rich Al-Si-Mg-Fe-Ce pentagonal system thermodynamic database, calculate the solid solution temperature curve of the Mg2Si age-strengthening phase, the equilibrium dissolution temperature of the AlSiCe rare earth phase, and the influence of Ce element on the Al matrix vacancy formation energy in the casting alloy.

[0042] S2. Based on the calculation results of step S1, select the temperature range between the full solid solution temperature of Mg2Si phase and the equilibrium dissolution temperature of AlSiCe rare earth phase as the solid solution treatment window, and perform solid solution treatment on the casting alloy within the solid solution treatment window.

[0043] S3. The alloy after the solution treatment in step S2 is quenched and cooled to form an Al-based supersaturated solid solution.

[0044] S4. Perform artificial aging treatment on the alloy after quenching in step S3. The aging temperature is determined based on the influence of Ce element on the vacancy formation energy of Al matrix calculated in step S1.

[0045] The pentaneous system thermodynamic database mentioned in step S1 is constructed based on the CALPHAD method, and the thermodynamic model parameters of each equilibrium phase are fitted by the PARROT optimization module.

[0046] The casting alloy to be treated in step S1 belongs to the Al-Si-Mg-Fe-Ce pentagonal alloy system, wherein the amount of Ce added is 0.2-1.8 wt.%.

[0047] In step S1, the isothermal cross-sectional phase equilibrium data of the Al-Fe-Ce ternary system in the thermodynamic database is combined with the thermodynamic data of the Al-Si-Mg, Al-Si-Fe, Al-Si-Ce, Al-Mg-Fe, and Al-Mg-Ce binary and ternary subsystems. The thermodynamic description parameters of the AlSiCe rare earth phase in the Al-Si-Mg-Fe-Ce pentagonal system are obtained by CALPHAD extrapolation. Based on these thermodynamic description parameters, the equilibrium dissolution temperature of the AlSiCe rare earth phase is determined.

[0048] The selection of the solid solution treatment window in step S2 is based on the following criteria: the solid solution temperature is set above the complete solid solution temperature of the Mg2Si phase calculated by the thermodynamic database and below the equilibrium dissolution temperature of the AlSiCe rare earth phase.

[0049] In step S2, the solution treatment temperature is 520-545℃.

[0050] In step S2, the heat preservation time for the solution treatment is 6-12 hours.

[0051] In step S3, the quenching medium for quenching and cooling is water or a mixture of ice and water, and the quenching transfer time does not exceed 15 seconds.

[0052] The heat preservation time for artificial aging treatment in step S4 is 4-10 hours.

[0053] The aging temperature for the artificial aging process in step S4 is 160-190℃.

[0054] The working mechanism and principle of each step in this invention:

[0055] I. Selection of solution treatment window and microstructure evolution (steps S1-S2)

[0056] The solution temperature window is defined by the complete solution temperature of the Mg2Si phase as the lower limit and the equilibrium dissolution temperature of the AlSiCe rare earth phase as the upper limit. This range allows the solution treatment to simultaneously meet two microstructure control objectives. Above the Mg2Si solution temperature, the coarse Mg2Si phase in the as-cast state decomposes, and Mg and Si atoms diffuse into the α-Al matrix to form a substitutional solid solution, eliminating as-cast compositional segregation and providing solute supersaturation for subsequent aging. Below the AlSiCe equilibrium dissolution temperature, the thermodynamic stability of this rare earth phase is maintained during the solution holding process. The AlSiCe phase precipitates preferentially over α-Al during solidification. During solution holding, AlSiCe particles distributed at grain boundaries and phase boundaries exert a Zener pinning effect on grain boundary migration, inhibiting thermally activated grain growth and preserving the fine-grained structure of Ce obtained in the as-cast state through heterogeneous nucleation and compositional supercooling.

[0057] When held at a selected temperature window, the eutectic Si undergoes an interfacial energy-driven morphological evolution. The sharp corners of the lamellar eutectic Si have higher chemical potentials and preferentially dissolve. Solute atoms redeposit on the smooth surface via short-range diffusion, driving the overall morphology to transform from lamellar to near-spherical particles, thus eliminating the notch effect generated by sharp eutectic Si under load.

[0058] II. Quenching and Cooling (Step S3)

[0059] After solution treatment, rapid quenching with water or an ice-water mixture is performed. The purpose of strictly controlling the transfer time is to allow the alloy to quickly transition from the solution temperature to the intermediate temperature range, avoiding uncontrolled pre-precipitation of Mg and Si atoms that would consume supersaturation. Rapid cooling simultaneously freezes the thermal equilibrium vacancies and solute atoms obtained during the solution treatment stage into the matrix. The supersaturated vacancies become the main mediators of solute atom diffusion during subsequent aging, playing a key role in accelerating the nucleation rate of precipitated phases.

[0060] III. Enhancement of Human Resource Efficiency and Collaboration (Step S4)

[0061] The aging temperature is determined based on the influence of Ce on the vacancy formation energy of the Al matrix. The role of rare-earth Ce in the aging stage is manifested on three levels. First, when Ce exists in the α-Al lattice in a substitutional solid solution manner, the difference in atomic radius between Ce and Al causes significant lattice distortion in the surrounding area. This distortion field interacts elastically with the strain field around Mg and Si atoms, lowering the nucleation barrier of Mg-Si solute clusters. Second, dissolved Ce atoms can reduce the matrix vacancy formation energy, increase the thermal equilibrium vacancy concentration, and directly accelerate the diffusion rate of Mg and Si atoms and the precipitation kinetics of the β″-Mg2Si phase. Third, within the selected aging temperature range, some dissolved Ce atoms precipitate from the supersaturated solid solution as an Al-Ce-Si ternary coherent precipitate, maintaining a coherent or semi-coherent lattice matching relationship with the α-Al matrix.

[0062] During the aging process, needle-like β″-Mg2Si phase and spherical Al-Ce-Si coherent phase are formed simultaneously in the matrix. The β″-Mg2Si phase exerts a strong pinning effect on dislocation slip through the coherent strain field between itself and the matrix, which constitutes the main contribution to precipitation strengthening; the Al-Ce-Si coherent particles provide isotropic strengthening increments in all directions, forming a complementary dislocation hindering network with the β″-Mg2Si phase.

[0063] In summary, this method, through thermodynamic calculations, synergistically satisfies two conditions during the solid solution stage: sufficient solid solution of Mg2Si and stable existence of the AlSiCe phase. During the aging stage, it simultaneously utilizes the dual mechanisms of Ce reducing vacancy formation energy to accelerate precipitation and directly forming nano-coherent phases, thus constructing a microstructure synergistically strengthened by β″-Mg2Si and Al-Ce-Si nanophases.

[0064] To make the present invention more fully disclosed, more specific embodiments are described below.

[0065]

[0066] Note: In the table above, GHSERAL, GHSERFE, and GHSERCE are the Gibbs free energies of the pure element reference state, taken from the SGTE database. Other binary interaction parameters of the boundary binary systems (Al-Fe, Al-Ce, Ce-Fe) and the Liquid phase are all derived from existing mature literature and directly adopted after compatibility verification in this study. All parameters in the table above were obtained through optimization using experimental data in this study and are the core parameters for constructing the self-consistent Al-Fe-Ce ternary database in this invention.

[0067] Example 1

[0068] Step S1: Provide the rare-earth Ce-modified Al-Si-Mg based casting alloy to be treated. The alloy composition is Si 7.08 wt.%, Mg 0.46 wt.%, Fe 1.03 wt.%, Ce 1.65 wt.%, with the balance being Al and unavoidable impurities. Utilize the Al-rich Al-Si-Mg-Fe-Ce pentagonal system thermodynamic database, constructed based on the CALPHAD method. The thermodynamic model parameters of each equilibrium phase are obtained by fitting using the PARROT optimization module. The solid solution temperature curve of the Mg2Si age-strengthening phase, the equilibrium dissolution temperature of the AlSiCe rare-earth phase, and the influence of Ce on the vacancy formation energy of the Al matrix are calculated using the thermodynamic database. The calculation results show that the total solid solution temperature of the Mg2Si phase is 512℃, the equilibrium dissolution temperature of the AlSiCe rare-earth phase is 556℃, and the addition of Ce reduces the vacancy formation energy of the Al matrix to 0.53 eV. Specifically, the phase equilibrium data of the 873K isothermal section of the Al-Fe-Ce ternary system, combined with the thermodynamic data of the binary and ternary subsystems of Al-Si-Mg, Al-Si-Fe, Al-Si-Ce, Al-Mg-Fe, and Al-Mg-Ce, were extrapolated using CALPHAD to obtain the thermodynamic description parameters of the AlSiCe rare earth phase in the Al-Si-Mg-Fe-Ce pentagonal system. Based on these thermodynamic description parameters, the equilibrium dissolution temperature of the AlSiCe rare earth phase was determined.

[0069] Step S2: Based on the calculation results of S1, the temperature range between the complete solution temperature of the Mg2Si phase and the equilibrium dissolution temperature of the AlSiCe rare earth phase is selected as the solution treatment window. To balance the complete solution of the Mg2Si phase and the thermal stability of the AlSiCe rare earth phase within this window, a solution treatment temperature of 536℃ and a holding time of 8h are selected. The as-cast sample of the alloy is placed in a resistance furnace and held at 536℃ for 8h for solution treatment, allowing the Mg2Si phase to fully dissolve back into the α-Al matrix while maintaining the thermal stability of the AlSiCe rare earth phase, ensuring that it does not completely dissolve during the solution treatment process.

[0070] Step S3: Remove the alloy sample after S2 solution treatment from the resistance furnace and immediately transfer it to an ice-water mixture for quenching and cooling. The quenching transfer time is 8s to form a supersaturated Al matrix solid solution.

[0071] Step S4: The alloy sample, after being quenched and cooled in S3, is transferred to an aging furnace for artificial aging treatment. Based on the influence of Ce element on the vacancy formation energy of the Al matrix calculated in S1, the aging temperature is determined to be 177℃, and the aging holding time is 7h. After the above heat treatment process, a heat-treated alloy sample is obtained and its performance is tested.

[0072] Example 2

[0073] Step S1: The difference between this embodiment and Example 1 is that the amount of Ce added in the alloy composition is 1.80 wt.%, while the rest of the alloy composition is the same as in Example 1. Calculations were performed using the same thermodynamic database as in Example 1, and the total solid solution temperature of the Mg2Si phase was 512℃, the equilibrium dissolution temperature of the AlSiCe rare earth phase was 557℃, and Ce reduced the vacancy formation energy of the Al matrix to 0.55 eV.

[0074] Step S2: Based on the calculation results of S1, the solution treatment temperature is selected as 538℃ and the holding time is 6h. The as-cast sample of the cast alloy is placed in a resistance furnace and held at 538℃ for 6h for solution treatment.

[0075] Step S3: Same as in Example 1, the quenching transfer time is 8s.

[0076] Step S4: Based on the vacancy formation energy calculated in S1, the aging temperature is determined to be 174℃, and the aging holding time is 6h. After the above heat treatment process, a heat-treated alloy sample is obtained and its performance is tested.

[0077] Example 3

[0078] Step S1: The difference between this embodiment and Example 1 is that the amount of Ce added in the alloy composition is 1.50 wt.%, while the rest of the alloy composition is the same as in Example 1. Calculation results show that the complete solid solution temperature of the Mg2Si phase is 513℃, the equilibrium dissolution temperature of the AlSiCe rare earth phase is 554℃, and Ce reduces the vacancy formation energy of the Al matrix to 0.51 eV.

[0079] Step S2: Based on the calculation results of S1, the solution treatment temperature is selected as 534℃ and the holding time is 9h. The as-cast sample of the cast alloy is placed in a resistance furnace and solution treated at 534℃ for 9h.

[0080] Step S3: Same as in Example 1, the quenching transfer time is 8s.

[0081] Step S4: Based on the vacancy formation energy calculated in S1, the aging temperature is determined to be 179℃, and the aging holding time is 7h. After the above heat treatment process, a heat-treated alloy sample is obtained and its performance is tested.

[0082] Example 4

[0083] Step S1: The difference between this embodiment and Example 1 is that the amount of Ce added in the alloy composition is 1.00 wt.%, while the rest of the alloy composition is the same as in Example 1. Calculation results show that the complete solid solution temperature of the Mg2Si phase is 514℃, the equilibrium dissolution temperature of the AlSiCe rare earth phase is 549℃, and Ce reduces the vacancy formation energy of the Al matrix to 0.48 eV.

[0084] Step S2: Based on the calculation results of S1, the solution treatment temperature is selected as 532℃ and the holding time is 10h. The as-cast sample of the cast alloy is placed in a resistance furnace and solution treated at 532℃ for 10h.

[0085] Step S3: Same as in Example 1, the quenching transfer time is 8s.

[0086] Step S4: Based on the vacancy formation energy calculated in S1, the aging temperature is determined to be 181℃, and the aging holding time is 7h. After the above heat treatment process, a heat-treated alloy sample is obtained and its performance is tested.

[0087] Example 5 Step S1: The difference between this embodiment and Example 1 is that the amount of Ce added in the alloy composition is 0.60 wt.%, while the rest of the alloy composition is the same as in Example 1. Calculation results show that the complete solid solution temperature of the Mg2Si phase is 515℃, the equilibrium dissolution temperature of the AlSiCe rare earth phase is 543℃, and Ce reduces the vacancy formation energy of the Al matrix to 0.44 eV.

[0088] Step S2: Based on the calculation results of S1, the solution treatment temperature is selected as 529℃ and the holding time is 11h. The as-cast sample of the cast alloy is placed in a resistance furnace and solution treated at 529℃ for 11h.

[0089] Step S3: Same as in Example 1, the quenching transfer time is 8s.

[0090] Step S4: Based on the vacancy formation energy calculated in S1, the aging temperature is determined to be 184℃, and the aging holding time is 8h. After the above heat treatment process, a heat-treated alloy sample is obtained and its performance is tested.

[0091] Example 6

[0092] Step S1: The difference between this embodiment and Example 1 is that the amount of Ce added in the alloy composition is 0.20 wt.%, while the rest of the alloy composition is the same as in Example 1. Calculation results show that the complete solid solution temperature of the Mg2Si phase is 516℃, the equilibrium dissolution temperature of the AlSiCe rare earth phase is 537℃, and Ce reduces the vacancy formation energy of the Al matrix to 0.41 eV.

[0093] Step S2: Based on the calculation results of S1, the solution treatment temperature is selected as 526℃ and the holding time is 12h. The as-cast alloy sample is placed in a resistance furnace and solution treated at 526℃ for 12h.

[0094] Step S3: Same as in Example 1, the quenching transfer time is 8s.

[0095] Step S4: Based on the vacancy formation energy calculated in S1, the aging temperature is determined to be 186℃, and the aging holding time is 9h. After the above heat treatment process, a heat-treated alloy sample is obtained and its performance is tested.

[0096] Comparative Example 1

[0097] This comparative example provides an Al-Si-Mg based cast alloy to be treated, with the alloy composition of Si 7.08 wt.%, Mg 0.46 wt.%, Fe 1.03 wt.%, Ce 0.00 wt.%, and the balance being Al and unavoidable impurities. The alloy was subjected to heat treatment: solution treatment at 536℃ for 8 hours, quenching medium of an ice-water mixture, quenching transfer time of 8 seconds, and artificial aging at 177℃ for 7 hours. After the above heat treatment process, a heat-treated alloy sample was obtained and its performance was tested.

[0098] (a) Test Results

[0099]

[0100] (II) Data Analysis and Comparison

[0101] 1. Tensile strength and yield strength analysis

[0102] As shown in Table 2, the tensile strength of Examples 1-6 ranges from 239.5 to 268.3 MPa, and the yield strength ranges from 192.8 to 216.7 MPa; while the tensile strength of Comparative Example 1 is only 146.0 MPa, and the yield strength is only 118.0 MPa. The tensile strength of Example 1 is 83.77% higher than that of Comparative Example 1, and the yield strength of Example 1 is 83.64% higher than that of Comparative Example 1.

[0103] The strength advantage of Example 1 stems from the quantitative design of the solution temperature window and aging temperature. Step S1 calculates the full solution temperature of the Mg2Si phase and the equilibrium dissolution temperature of the AlSiCe rare earth phase. Step S2 selects a solution temperature within the window between these two values, allowing the Mg2Si phase to fully re-dissolve while preventing the AlSiCe phase from completely dissolving, allowing the latter to continue its solidification effect on Fe impurities. Step S1 also calculates that Ce reduces the vacancy formation energy in the Al matrix. Step S4 determines the aging temperature based on this, allowing Ce atoms to precipitate in a controlled manner as nanoscale Al-Ce-Si coherent precipitates, which, together with the β″-Mg2Si aging strengthening phase, are dispersed throughout the matrix, creating multiple pinning effects on dislocation movement.

[0104] Examples 2-6 used different Ce addition amounts. Step S1 in each example was based on calculations using a pentagonal thermodynamic database to obtain the corresponding thermodynamic parameters. Step S2 selected the solution temperature within each calculation window. Step S4 determined the aging temperature based on vacancy formation energy. As the Ce content decreased, the volume fraction of the AlSiCe rare earth phase and the Fe solidification capacity gradually decreased, resulting in a gradient decrease in the combined effect of precipitation strengthening and rare earth precipitation strengthening. In Example 2, because the Ce content was close to the upper limit of the protection range, a small amount of coarse primary rare earth phases had begun to appear in the microstructure, and the performance was lower than in Example 1. In Example 6, because the Ce content was close to the lower limit of the protection range, the number of AlSiCe rare earth phases was significantly reduced, the Fe solidification capacity was insufficient, and the higher aging temperature led to a tendency for coarsening of the precipitated phases, resulting in the lowest overall performance among all examples.

[0105] Comparative Example 1, without the thermodynamic calculations performed in step S1, used industry-experienced values ​​for both solution and aging temperatures. Both solution and aging times were too short, resulting in insufficient re-dissolution of the Mg2Si phase and insufficient precipitate density. The excessively long quenching transfer time led to low supersaturation. Furthermore, Comparative Example 1 lacked Ce, resulting in the absence of AlSiCe rare earth phase formation. Fe impurities precipitated extensively at grain boundaries as needle-like β-Al5FeSi harmful phases, disrupting matrix continuity and becoming stress concentration sources and crack initiation nuclei. These factors led to a significantly lower strength in Comparative Example 1. This comparison demonstrates that the three thermodynamic calculation results provided in step S1, transformed into process decisions through steps S2 and S4, are the core technical basis for achieving superior mechanical properties using this method.

[0106] 2. Post-fracture elongation analysis

[0107] As shown in Table 2, the elongation after fracture of Examples 1-6 was 1.8%-2.4%, while that of Comparative Example 1 was 2.2%. The elongation of Example 1 was 9.09% higher than that of Comparative Example 1.

[0108] The elongation advantage of Example 1 stems from three microstructural features: First, the solution temperature in step S2 is lower than the equilibrium solution temperature of the AlSiCe rare earth phase, which maintains thermal stability, continuously solidifies Fe impurities, and inhibits the regeneration of the needle-like β-Al5FeSi harmful phase; Second, the elongated AlSiCe rare earth phase in the as-cast microstructure undergoes interfacial energy-driven spheroidization during the solution treatment and heat preservation process, transforming into near-spherical particles, significantly reducing the interfacial stress concentration with the matrix; Third, the aging temperature in step S4 is determined based on the vacancy formation energy calculation results, and Ce precipitates uniformly in the form of a nano-coherent phase, without forming a coarse continuous phase at the grain boundaries, thus avoiding grain boundary embrittlement.

[0109] It should be noted that the elongation of Comparative Example 1 is similar to that of Examples 3 and 4, but its tensile strength is only 146.0 MPa, while the tensile strengths of Examples 3 and 4 reach 261.8 MPa and 253.6 MPa, respectively. This indicates that Comparative Example 1 achieved limited plasticity at a lower strength level, rather than reflecting the intrinsic plasticity of the material. All examples maintained elongation similar to or better than Comparative Example 1 despite a significant increase in strength, indicating that a synergistic improvement in strength and plasticity was indeed achieved. Example 6 had the lowest elongation among all examples, which is related to its low Ce content, insufficient Fe curing, and high aging temperature leading to coarsening of the precipitated phase.

[0110] In Comparative Example 1, the Fe impurity exists at the grain boundaries in the form of a needle-like β-Al5FeSi harmful phase. This phase has a sharp interface morphology and intrinsic brittleness, and becomes a preferred crack initiation source under load. However, due to the low strength level of Comparative Example 1, the sample fractured before the crack propagation was fully developed, so its absolute elongation did not show an extremely low level. Figure 2 The SEM image shows the eutectic silicon particles in the heat-treated state of the alloy in Example 1. The particles are smaller, more rounded (tending towards granular), and more dispersed. Ce atoms may be adsorbed at the growth front of the eutectic Si, hindering the anisotropic growth of Si crystals, thus promoting the refinement and spheroidization of the eutectic Si. This morphological optimization greatly reduces the cutting effect of sharp Si particles on the matrix, reduces microcrack initiation, and thus improves the alloy's plasticity and toughness. Figures 3 to 7 These are surface distribution diagrams for Al, Si, Mg, Fe, and Ce, respectively. From... Figure 3 As can be seen, the red / orange high-intensity signal areas represent aluminum-rich regions, corresponding to... Figure 2 The continuous matrix in the image confirms that the matrix is ​​an α-Al solid solution. The blue "pore" areas in the image represent Al-depleted regions, corresponding to second-phase particles enriched with other elements. Figure 4 It is evident that the Si particles are small in size and have a rounded shape, indicating that the eutectic Si phase underwent spheroidization during the solid solution treatment. Figure 5It can be seen that only a small amount of Mg is enriched, with the majority distributed evenly in the matrix. (Comparison) Figure 6 and Figure 7 It can be seen that the enrichment regions of Fe and Ce coincide spatially, indicating that the AlSiCe rare earth phase maintains thermal stability within the solid solution treatment window and continues to play a role in solidifying Fe impurities.

[0111] 3. Hardness Analysis

[0112] As shown in Table 2, the hardness of Examples 1-6 is 157-183 HV, while the hardness of Comparative Example 1 is only 84 HV. The hardness of Example 1 is increased by 117.86% compared to Comparative Example 1.

[0113] Example 1 has the highest hardness because after the process of this invention, the α-Al matrix contains two nanoscale precipitates: β″-Mg2Si age-strengthening phase and Al-Ce-Si coherent precipitate. Both phases pin dislocation movement. When the indenter is pressed in, the dislocations need to bypass or cut through the dual obstacles, which macroscopically manifests as an increase in indentation resistance, i.e., hardness.

[0114] Comparative Example 1, lacking Ce, resulted in the absence of AlSiCe rare-earth phase formation and Ce's influence on vacancy formation energy. Its short solution and aging times led to insufficient precipitate density. Furthermore, the excessively long quenching and transfer time resulted in low concentrations of solute atoms and vacancies in the matrix. These factors resulted in the near absence of effective nano-precipitates in the α-Al matrix. Dislocation movement was primarily hindered by the coarse eutectic Si phase and acicular β-Al5FeSi phase remaining in the as-cast state. Their pinning efficiency for dislocations was far lower than that of the highly dispersed nano-coherent precipitates, thus resulting in the lowest hardness.

[0115] In each embodiment, as the Ce content decreases, the number of Ce atoms dissolved into the α-Al matrix decreases, the number of precipitable Al-Ce-Si coherent phases decreases, the promoting effect of Ce on the precipitation kinetics of Mg2Si weakens, and the hardness shows a gradual decreasing trend. The hardness of Example 6 is the lowest value among all embodiments, which is related to the Ce content being at the lower limit of the protection range and the insufficient number of AlSiCe rare earth phases. Figure 1 Transmission electron microscope (TEM) images of the alloy of Example 1 after the heat treatment process of this invention are shown. The upper right corner shows a selected area magnified morphology of the corresponding region, and the lower right corner shows the selected area electron diffraction pattern of the incident electron beam along the

[001] crystal orientation. Nanoscale Al-Ce-Si coherent / semi-coherent precipitates are dispersed in the α-Al matrix, while a high density of needle-like β″-Mg2Si age-strengthening phase exists. The two types of nanoscale precipitates together form a multi-pinned structure.

[0116] 4. Conductivity Analysis

[0117] As shown in Table 2, the conductivity of Examples 1-6 was 36.3%-39.2% IACS, while the conductivity of Comparative Example 1 was only 32.5% IACS. The conductivity of Example 1 was 20.62% higher than that of Comparative Example 1.

[0118] Example 1 exhibits the highest conductivity for two reasons. Firstly, the solution temperature in step S2 is above the full solution temperature of Mg₂Si and below the equilibrium dissolution temperature of AlSiCe. The aging temperature in step S4 is determined based on vacancy formation energy calculations. This ensures sufficient Mg and Si atoms to desolvent and precipitate, while Ce atoms precipitate in a controlled manner as a nano-coherent phase. Consequently, the concentration of residual solid solution solute in the α-Al matrix is ​​significantly reduced, weakening lattice scattering of conduction electrons. Secondly, the solidification effect of Ce on Fe impurities stabilizes Fe atoms within the AlSiCe rare-earth phase, reducing additional electron scattering caused by Fe atoms remaining in a solid solution state within the matrix.

[0119] Comparative Example 1, due to insufficient solid solution and aging, has a large number of solid-solid Mg and Si atoms remaining in the matrix, forming lattice distortion scattering centers; due to the lack of Ce addition, some Fe atoms remain in the matrix in a solid-solid state, further increasing the electron scattering source density and resulting in the lowest conductivity.

[0120] In each embodiment, as the Ce content decreases, the Fe solidification capacity of the AlSiCe rare earth phase decreases, the proportion of residual dissolved Fe atoms in the matrix increases, the promoting effect of Ce on the sufficiency of aging precipitation weakens, and the electrical conductivity shows a gradient decreasing trend. Example 6 has the lowest electrical conductivity among all examples, which is related to its low Ce content and high proportion of residual dissolved Fe atoms in the matrix. As a physical indicator sensitive to the concentration of dissolved atoms in the matrix, the change trend of electrical conductivity is consistent with the change trend of mechanical properties, verifying the promoting effect of the process of this invention on the sufficiency of aging precipitation from the perspective of electrical performance.

[0121] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for optimizing the heat treatment process of rare-earth Ce-modified Al-Si-Mg-based casting alloys based on computational thermodynamics, characterized in that, Includes the following steps: S1. Provide a rare earth Ce-modified Al-Si-Mg based casting alloy to be treated. Using the Al-rich Al-Si-Mg-Fe-Ce pentagonal system thermodynamic database, calculate the solid solution temperature curve of the Mg2Si age-strengthening phase, the equilibrium dissolution temperature of the AlSiCe rare earth phase, and the influence of Ce element on the Al matrix vacancy formation energy in the casting alloy. S2. Based on the calculation results of step S1, select the temperature range between the full solid solution temperature of Mg2Si phase and the equilibrium dissolution temperature of AlSiCe rare earth phase as the solid solution treatment window, and perform solid solution treatment on the casting alloy within the solid solution treatment window. S3. The alloy after the solution treatment in step S2 is quenched and cooled to form an Al-based supersaturated solid solution. S4. Artificial aging treatment is performed on the alloy after quenching in step S3. The aging temperature is determined based on the influence law of Ce element on the vacancy formation energy of Al matrix calculated in step S1. In step S2, the solution treatment temperature is 520-545℃; In step S2, the heat treatment time is 6-12 hours; In step S3, the quenching medium for quenching and cooling is water or a mixture of ice and water, and the quenching transfer time does not exceed 15 seconds. The heat preservation time for artificial aging treatment in step S4 is 4-10 hours; The aging temperature for the artificial aging process in step S4 is 160-190℃.

2. The method for optimizing the heat treatment process of rare-earth Ce-modified Al-Si-Mg-based casting alloys based on computational thermodynamics according to claim 1, characterized in that, The pentaneous system thermodynamic database mentioned in step S1 is constructed based on the CALPHAD method, and the thermodynamic model parameters of each equilibrium phase are fitted by the PARROT optimization module.

3. The method for optimizing the heat treatment process of rare-earth Ce-modified Al-Si-Mg-based casting alloys based on computational thermodynamics according to claim 1, characterized in that, The casting alloy to be treated in step S1 belongs to the Al-Si-Mg-Fe-Ce pentagonal alloy system, wherein the amount of Ce added is 0.2-1.8 wt.%.

4. The method for optimizing the heat treatment process of rare-earth Ce-modified Al-Si-Mg-based casting alloys based on computational thermodynamics according to claim 1, characterized in that, In step S1, the isothermal cross-sectional phase equilibrium data of the Al-Fe-Ce ternary system in the thermodynamic database is combined with the thermodynamic data of the Al-Si-Mg, Al-Si-Fe, Al-Si-Ce, Al-Mg-Fe, and Al-Mg-Ce binary and ternary subsystems. The thermodynamic description parameters of the AlSiCe rare earth phase in the Al-Si-Mg-Fe-Ce pentagonal system are obtained by CALPHAD extrapolation. Based on these thermodynamic description parameters, the equilibrium dissolution temperature of the AlSiCe rare earth phase is determined.

5. The method for optimizing the heat treatment process of rare-earth Ce-modified Al-Si-Mg-based casting alloys based on computational thermodynamics according to claim 1, characterized in that, The selection of the solid solution treatment window in step S2 is based on the following criteria: the solid solution temperature is set above the complete solid solution temperature of the Mg2Si phase calculated by the thermodynamic database and below the equilibrium dissolution temperature of the AlSiCe rare earth phase.